THE CHARACTERISTICS OF JAVANESE LANGUAGE IN BLORA DIALECT: A SOCIOLINGUISTICS STUDY - Audrizan Wahyu Suprapto; Didit Kurniadi; Eko Heriyanto (Universitas Aki, 2021)
Indonesia is a country that has many regional languages. The diversity of regional languages is a characteristic of Indonesia. One of them is the Javanese language which is used by the Javanese people and has a variety of dialects. Therefore, the writer is interested in conducting research on the characteristics of the Javanese dialect of Blora in accordance with sociolinguistic studies that examines the relationship between language and its speaking community. This is similar to the writer aim to analysis the differences between Blora, Temanggung and Mojokerto dialect. The writer also analyzes the use of Javanese speech level used by the people of Blora. This is because there are still many people who do not know the geographical location of Blora City. In this study, the writer uses a qualitative descriptive method and the data collection methods needed to analysis the data are simak method and cakap method. The analysis results showed that there are characteristics of the Blora dialect and there are differences between Blora, Temanggung and Mojokerto dialect. It can be concluded that the variations of the three dialects have different morphology, phonology, lexical and semantics. This is due to the diversity of dialect differences from the results of regional observations.